2014
DOI: 10.1080/03630242.2014.883660
|View full text |Cite
|
Sign up to set email alerts
|

Maternity in Spanish Elite Sportswomen: A Qualitative Study

Abstract: The aim of this qualitative phenomenological study was to describe the experiences of maternity among Spanish elite sportswomen. Twenty (n = 20) Spanish elite sportswomen with the following criteria were included: (a) aged 18-65 years; (b) had been pregnant during their sporting professional career; and (c) after the end of their pregnancy they had returned to their professional sporting career for at least one year. A qualitative analysis was conducted. Data were collected using in-depth personal interviews, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Previous research has also identified the struggle to manage two sometimes conflicting identities. Martinez-Pascual et al described how elite athletes felt their identity as a mother overtook their identity as a sportswoman and, as a result, many athletes described the guilt about trying to do both 19. Such identities are further compounded by the cultural and societal complexities of media portrayals of elite pregnant athletes 17.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has also identified the struggle to manage two sometimes conflicting identities. Martinez-Pascual et al described how elite athletes felt their identity as a mother overtook their identity as a sportswoman and, as a result, many athletes described the guilt about trying to do both 19. Such identities are further compounded by the cultural and societal complexities of media portrayals of elite pregnant athletes 17.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez-Pascual et al described how elite athletes felt their identity as a mother overtook their identity as a sportswoman and, as a result, many athletes described the guilt about trying to do both. 19 Such identities are further compounded by the cultural and societal complexities of media portrayals of elite pregnant athletes. 17 Most recently, Darroch et al identified the lack of support and uncertainty surrounding pregnancy and governmental funding/corporate sponsorship for elite pregnant athletes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have highlighted pregnancy and motherhood as the main reasons why female athletes may end their sportive career or fail to reach their full potential in sports [8,9]. Furthermore, the time required for competition and training as well as potential fears and doubts regarding their sportive future, may leave little time for motherhood [10]. Additionally, medical discourses that have positioned exercise and sport training during pregnancy as dangerous may also in uence an athlete´s decision of planning a pregnancy [11].…”
Section: Introductionmentioning
confidence: 99%